Quadro de antagônicos: aplicabilidade físico-energética no processo criador da Pequena Companhia de Teatro - MARCONCINE, José Cláudio (2022)
This article aims to analyze how the Antagonistic Table (QdA) consolidates itself in the creative processes of the Pequena Companhia de Teatro (PCT), based in São Luís, Maranhão, developed and applied on its actors' preparation. We will adopt as an analysis unit for this case study the shows: Entrelaços (2009); Pai&Filho (2010); and Velhos caem do céu como canivetes (2013). As complementary methodologies, we will proceed with: a review of the method adopted by the company for actors and actresses' training and their characters' composition; detailed actors and actresses' body ways in the representations construction, considering the applicability physical energetic of (QdA), through classes training; suggestion of systematization of the actors and actresses' creative process in their characters' composition, from the training proposed by PCT. The observations and studies in the actors and actresses' dramaturgy construction will be fixed, in the beginning, in the Theatre Anthropology by Barba (1995), in the Bodymedia Theory in Greiner and Katz (2005) and in the energetic perception in Moretti (2022). The instruments of data collection are the focused and semistructured interviews with the actors and director involved on those three shows (analysis unit of this search); and this researcher's notes of personal experiences in rehearsal room. The data resources are this researcher's natural participant observation; the three shows director's performance notebooks; PCT's blog; "The QdA as a training instrument for the actor" workshop handout; videos of the three shows in full; video records of the three stage productions/training; photos of the three shows; and bibliographical research. For the analysis of the collected data we will use the Discourse Textual Analysis (ATD). The final result will be the dissertation writing, the systematization of the creative process QdA into a virtual platform and a technical demonstration.